Two RecA Protein Types That Mediate Different Modes of Hyperrecombination - Baitin, Dmitry M. (American Society for Microbiology (ASM), 2008)
RecAX53 is a chimeric variant of the Escherichia coli RecA protein (RecAEc) that contains a part of the central domain of Pseudomonas aeruginosa RecA (RecAPa), encompassing a region that differs from RecAEc at 12 amino acid positions. Like RecAPa, this chimera exhibits hyperrecombination activity in E. coli cells, increasing the frequency of recombination exchanges per DNA unit length (FRE). RecAX53 confers the largest increase in FRE observed to date. The contrasting properties of RecAX53 and RecAPa are manifested by in vivo differences in the dependence of the FRE value on the integrity of the mutS gene and thus in the ratio of conversion and crossover events observed among their hyperrecombination products. In strains expressing the RecAPa or RecAEc protein, crossovers are the main mode of hyperrecombination. In contrast, conversions are the primary result of reactions promoted by RecAX53. The biochemical activities of RecAX53 and its ancestors, RecAEc and RecAPa, have been compared. Whereas RecAPa generates a RecA presynaptic complex (PC) that is more stable than that of RecAEc, RecAX53 produces a more dynamic PC (relative to both RecAEc and RecAPa). The properties of RecAX53 result in a more rapid initiation of the three-strand exchange reaction but an inability to complete the four-strand transfer. This indicates that RecAX53 can form heteroduplexes rapidly but is unable to convert them into crossover configurations. A more dynamic RecA activity thus translates into an increase in conversion events relative to crossovers.